Styles of Representation in Constituencies in the Homeland and Abroad: The Case of Italy. Issue 1 (30th November 2020) - Østergaard-Nielsen, Eva; Camatarri, Stefano
Abstract: The role orientation of political representatives and candidates is a longstanding concern in studies of democratic representation. The growing trend in countries to allow citizens abroad to candidate in homeland elections from afar provides an interesting opportunity for understanding how international mobility and context influences ideas of representation among these emigrant candidates. In public debates, emigrant candidates are often portrayed as delegates of the emigrant constituencies. However, drawing on the paradigmatic case of Italy and an original data set comprising emigrant candidates, we show that the perceptions of styles of representation abroad are more complex. Systemic differences between electoral districts at home and abroad are relevant for explaining why and how candidates develop a trustee or delegate orientation.